2010
DOI: 10.1016/j.biocel.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Rab1 GTPase promotes expression of β-adrenergic receptors in rat pulmonary microvascular endothelial cells

Abstract: It is known that Rab1 regulates the expression and function of beta-adrenoceptors (β-ARs) in many cells. However, the effect of these changes in rat pulmonary microvascular endothelial cells (RPMVECs) is not known. In the present study, we investigated the role of Rab1, a Ras-like GTPase that coordinates protein transport from the endoplasmic reticulum (ER) to the Golgi body and regulates the cell-surface targeting and function of endogenous β-ARs in RPMVECs in the presence of lipopolysaccharide (LPS). We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…Inactivation of Rab GTPases induces the mistrafficking of GPCRs, which leads to the dysfunction of the receptors that is directly linked to disorder of cell function 3, 4, 44. Consistent with other studies 3, 4, 44, our study showed that Rab26 silencing with siRab26-DYM in LPS stimulated cells increased the surface levels of TLR4 and subsequently activated TLR4 signal pathway in primary HPMVECs. Up-regulation of Rab26 expression with an adenovirus partially reversed the LPS induced activation of TLR4 signal pathway.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inactivation of Rab GTPases induces the mistrafficking of GPCRs, which leads to the dysfunction of the receptors that is directly linked to disorder of cell function 3, 4, 44. Consistent with other studies 3, 4, 44, our study showed that Rab26 silencing with siRab26-DYM in LPS stimulated cells increased the surface levels of TLR4 and subsequently activated TLR4 signal pathway in primary HPMVECs. Up-regulation of Rab26 expression with an adenovirus partially reversed the LPS induced activation of TLR4 signal pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that Rab26 plays an important role in regulating the transport of α2-ARs from the Golgi to the membrane 9, lysosome trafficking and mitochondrial redistribution 10 and induces the autophagy of neuronal somata 11. As shown in our previous study, the GTPases Rab1 and Rab5a control the permeability of HPMVECs by regulating the trafficking and localization of the β-AR 3, 4. However, whether Rab26 regulates the permeability of HPMVECs remains unclear.…”
Section: Introductionmentioning
confidence: 71%
“…Wild type Rab1-pcDNA3 (Rab1WT), pcDNA3 plasmid, pDsRed2-ER, an ER marker, AT1R-pCDM8 tagged with green fluorescent protein (GFP-AR1T) and AT1R tagged with hemagglutinin (HA-AT1R) were kind gifts of Dr. Wu (Department of Pharmacology and Experimental Therapeutics, Louisiana State University Health Sciences Center, New Orleans, Louisiana). All other materials were described elsewhere (Wang et al, 2008; Li et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…The Rab1 effects on the cell-surface export of β 2 -AR and AT1R are more complicated than the effects on other GPCRs. Overexpression of Rab1 enhanced the cell-surface transport of endogenous β 2 -AR in endothelial cells [16] but had no effect on exogenous β 2 -AR in HEK293 cells [15] or endogenous β 2 -AR in cardiomyocytes [14]. Rab1 expression increased the cell-surface expression of endogenous AT1R in cardiomyocytes [18] and endothelial cells [19] without influencing exogenously expressed AT1R in HEK293 cells [15].…”
Section: Rab Gtpases In the Transport Of Gpcrs From The Er To The Celmentioning
confidence: 99%